Analisis Rasio Keuangan Berbasis SAP terhadap Kinerja dan Akuntabilitas Keuangan Daerah : Studi Kasus pada Pemerintah Kota Bengkulu Tahun 2021-2024 - Fathul Hilal Perdana Kusuma; Nina Yulianasari; Imellia Chelomitha; Alkerina Sindi Delvia; Vira Naila Fenita; Putri Herlianti; Meisyah Rahel Gracella; Resty Made Pertiwi; Aris Dwi Saputra; Dona Oktaviani (Inisiatif: Jurnal Ekonomi, Akuntansi dan Manajemen, 2026)
This study aims to examine the implementation of financial ratio analysis based on Government Accounting Standards (SAP) in relation to the financial performance and accountability of the Bengkulu City Government for 2021–2024. Financial ratio analysis is an important instrument in measuring the effectiveness, efficiency, independence, and accountability of regional financial management. The study adopted a descriptive quantitative approach using secondary data obtained from the Bengkulu City Regional Financial Report (LKPD). The analytical methods applied included the regional financial independence ratio, effectiveness ratio, efficiency ratio, and activity ratio. The findings of this study indicate that the financial performance of the Bengkulu City Government generally improved during the observation period. The effectiveness ratio indicates an increase in the realization of regional original revenue, while the efficiency ratio reflects improved expenditure management. However, the level of regional financial independence remains relatively low, with regional revenues still dependent on central government transfers. From an accountability perspective, the implementation of SAP contributes significantly to the quality of transparency and accountability in regional financial reports. This study implies that optimization of regional original revenue and improvement of budget management are necessary to support sustainable regional financial performance and accountability.